CERITA RAKYAT SEBAGAI UPAYA PEMILIHAN BAHAN AJAR APRESIASI BAHASA DAN SASTRA INDONESIA - Sobri Sobri; Maman Rukmana (Jurnal Membaca Bahasa dan Sastra Indonesia, 2021)
Abstract:The problems in this paper are the criteria, and steps to arrange teaching material by using local folklore. The aims of this paper are to describe, and how to arrange language and Indonesian literature teaching materials source from the south Banten folklore for elementary school students in Pandeglang district. The method of this research is descriptive-analysis. Questionnaire technique is used to capture the teachers' opinion about the criteria and steps to make folklore as teaching materials. Folklore teaching materials of South Banten has fulfilled adequate criteria and considered the steps in arranging teaching materials. In the end to anticipate the limited teaching materials in the form of folklore from own region, the language and Indonesian literature teachers at an elementary school in Pandeglang can utilize it as an alternative and variety of teaching material.Keywords: folklore, and teaching materials. Abstrak:Permasalahan dalam tulisan ini adalah kriteria, dan langkah-langkah menyusun bahan ajar cerita rakyat. Tujuannya untuk mendeskripsikan cara menyusun bahan ajar bahasa dan sastra Indonesia yang bersumber dari cerita rakyat Banten Selatan bagi siswa sekolah dasar di Kabupaten Pandeglang.Metode penelitian yang digunakan deskriptif-analitis. Teknik angket digunakan untuk menjaring pendapat guru tentang kriteria dan langkah-langkah menyusun bahan ajar cerita rakyat. Hasilnya, bahan ajar cerita rakyat Banten Selatan telah memenuhi kriteria yang memadai serta memperhatikan langkah-langkah dalam menyusun bahan ajar.Pada akhirnya antisipasi kekurangtersediaan bahan pembelajaran berupa cerita rakyat dari daerah sendiri, guru bahasa dan sastra Indonesia SD di Kabupaten Pandeglang dapat mempergunakannya sebagai alternatif dan variasi bahan pembelajaran.Kata Kunci: cerita rakyat, dan bahan ajar